Efficiency investigation of SS and SP compensation topologies for wireless power transfer - Rehman, Masood; Nallagownden, Perumal; Baharudin, Zuhairi (Institute of Advanced Engineering and Science, 2019)
Wireless power transfer (WPT) using inductive and resonant coupling has been widely explored in recent years for ease and safety over conventional cable charging systems. The efficiency of WPT systems is reducing drastically due to an increase in air-gaps and misalignment between transmitter (Tx) and receiver (Rx). Many circuit topologies have been analyzed to improve the efficiency of WPT system based on symmetrical coils. However, the circuit topologies have not been studied widely for unsymmetrical coils. This paper presents the investigation of two fundamental topologies i.e. Series-Series (SS) and Series-Parallel (SP) for unsymmetrical coils as well as symmetrical coils. Theoretical analysis of both the compensation topologies have been accomplished, then modeling of both the topologies have been done using two different combination of circular coils. In first case, two similar size coils have been designed and in second case transmitter coil of higher dimensions than receiver coil is designed. The efficiency of the system has been analyzed at multiple distances in both cases by integrating coil structure with the circuit. The overall result show that when Tx is bigger than Rx, the SP topology gives better efficiency than SS counterpart.